Beam generation and structural optimization of size-selected Au923 clusters. Issue 7 (9th June 2020) - Lu, Siqi; Hu, Kuojuei; Zuo, Zewen; Hu, Shengyong; Wang, Guanghou; Song, Fengqi; Cao, Lu
Abstract : We show the feasibility to control the structure of gold cluster Au923 in a large range. Abstract : A size-selected beam of Au923±20 clusters is generated in a gas-phase condensation cluster source equipped with a lateral time-of-flight mass selector. The beam current reaches up to 9.13 nA for small clusters and 80 pA for Au923±20 clusters, which are then analyzed using a scanning transmission electron microscope. Four types of metastable structures are observed for the Au923±20 clusters, including ino-decahedron (Dh), cuboctahedron and icosahedron (Ih). The proportion of bulk-favorable cuboctahedron ( i.e. face center cubic (Fcc)) structure takes up only 10–20%, while the penta-rotating symmetrical structures (Dh/Ih) are the dominant ones which take up over three quarters. Changing the beam condition may optimize the clusters from Dh-dominant to the Ih-dominant phase, which paves the way towards nanoparticle control beyond the diameters.